Estudo sistêmico-funcional da estrutura lógica de artigos de revista em inglês - Soares, João Paulo (2008)
As part of the wider context of Project DIRECT: Em direção à linguagem do trabalho (PUC-SP/LAEL), this study aims at investigating grammatical elements that contribute to text cohesion and organization, both below (verbal and nominal group) and above clause (conjunction and pronominal reference), in the framework of Systemic-Functional Grammar (Halliday, 1994). It analyses the text structures (the logical metafunction) of two magazines: the North American Newsweek and the specifically directed to EFL (English as a Foreign Language) students, the Brazilian version of Speak up. The study makes use of the computational program Wordsmith Tools (Scott, 1999). Results show that the Speak up texts have a structure with more elements of what Bathia (1983) calls language simplification, characterized by lesser complexity in logical terms: more simple verb tenses, usually only represented as suffix in the process (simple past, present and future tenses); more nominal groups with premodifiers and postmodifiers with prepositional phrases; more coordinate conjunctions and first-person pronouns, whereas the Newsweek texts evidence greater linguistic elaboration in terms of textual complexity due to the frequent use of: complex verbal tenses, with auxiliaries (perfect and progressive tenses, future with going to and passive); lexically-dense nominal groups due to extensions resulting from information chaining through the construction of successive nominalizations and defining relatives clauses; besides reduced clauses, subordinate conjunctions and thirdperson pronouns